Gamification-Based Cooperative Learning Model: Optimizing Learning Motivation in Islamic Religious Education - Zahra, Desti; A. Gani, A. Gani; Wahyudi, Didik; Azizah, Nurul; Fatoni, Ilham (Journal of Educational Sciences, 2026)
Learning motivation is an essential factor that plays a role in increasing student involvement and success in the learning process, especially in Islamic Religious Education (PAI) subjects. Low student motivation to learn requires learning innovations that are able to create an active and fun learning atmosphere. This study aims to analyze the influence of gamification-based cooperative learning using Wordwall media on students' learning motivation in the Qur'an and Hadith materials as a Guideline for Life. This study uses a quantitative approach with a quasi experimental post-test only control group design. The research sample amounted to 62 grade VII students of SMP Negeri 3 Martapura consisting of an experimental class and a control class. Data was collected using a learning motivation questionnaire that had been tested for validity and reliability, then analyzed through normality tests, homogeneity tests, and Independent Samples T-Test. The results of the analysis showed a significance value of 0.022 (< 0.05), which indicated a significant difference in learning motivation between the two groups. Thus, gamification-based cooperative learning using Wordwall media has a positive effect on increasing student learning motivation.